Do Alimony Regulations Matter inside Marriage? Evidence from the 2008 Reform of the German Maintenance Law - Marianna Schaubert (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This study investigates how West German spouses have responded by adjusting their time allocation to the alimony reform introduced in 2008. This reform imposed financial self-responsibility after a finalized divorce. It weakened the relative bargaining position of the spouse with a claim for maintenance in the case of a potential divorce prior to the law change. Therefore, the present study helps to verify bargaining models by considering the 2008 policy change as a shift of spousal bargaining power. Estimating di_erence-in-di_erences models I find that, indeed, wives who face a potential low alimony loss might have increased their working hours as a result of the 2008 reform. To my knowledge, the present investigation is the first analysis of the behavioral response of individuals in longer marriages to the 2008 reform. Its approach to identifying those who have been (dis)advantaged by this reform is a new one, proposing a method that reflects the realities of alimony arrangements in Germany.
Keywords: D13; J12; J13; J22; K36; 330; Alimony; family; bargaining; institutional change; labor supply; time allocation